Airway opening pressure maneuver to detect airway closure in mechanically ventilated pediatric patients - Rodriguez Guerineau, Luciana; Vieira, Fernando; Rodrigues, Antenor; Reise, Katherine; Todd, Mark; Guerguerian, Anne-Marie; Brochard, Laurent (Frontiers in Pediatrics, 2024)
Background Airway closure, which refers to the complete collapse of the airway, has been described under mechanical ventilation during anesthesia and more recently in adult patients with acute respiratory distress syndrome (ARDS). A ventilator maneuver can be used to identify airway closure and measure the pressure required for the airway to reopen, known as the airway opening pressure (AOP). Without that maneuver, AOP is unknown to clinicians. Objective This study aims to demonstrate the technical adaptation of the adult maneuver for children and illustrate its application in two cases of pediatric ARDS (p-ARDS). Methods A bench study was performed to adapt the maneuver for 3–50 kg patients. Four maneuvers were performed for each simulated patient, with 1, 2, 3, and 4 s of insufflation time to deliver a tidal volume (Vt) of 6 ml/kg by a continuous flow. Results Airway closure was simulated, and AOP was visible at 15 cmH2O with a clear inflection point, except for the 3 kg simulated patient. Regarding insufflation time, a 4 s maneuver exhibited a better performance in 30 and 50 kg simulated patients since shorter insufflation times had excessive flowrates (>10 L/min). Below 20 kg, the difference in resistive pressure between a 3 s and a 4 sec maneuver was negligible; therefore, prolonging the maneuver beyond 3 s was not useful. Airway closure was identified in two p-ARDS patients, with the pediatric maneuver being employed in the 28 kg patient. Conclusions We propose a pediatric AOP maneuver delivering 6 ml/kg of Vt at a continuous low-flow inflation for 3 s for patients weighing up to 20 kg and for 4 s for patients weighing beyond 20 kg.